2021
DOI: 10.1371/journal.pone.0257567
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of hospital readiness during the COVID-19 pandemic in Nigeria

Abstract: Introduction The COVID-19 pandemic continues to overwhelm health systems across the globe. We aimed to assess the readiness of hospitals in Nigeria to respond to the COVID-19 outbreak. Method Between April and October 2020, hospital representatives completed a modified World Health Organisation (WHO) COVID-19 hospital readiness checklist consisting of 13 components and 124 indicators. Readiness scores were classified as adequate (score ≥80%), moderate (score 50–79.9%) and not ready (score <50%). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 5 publications
1
18
0
5
Order By: Relevance
“… 20 Usually, just like in other country, a designated hospital representative was in charge of filling out the checklist. 5 Coordination among hospital units is also difficult due to a lack of technical instruction. Furthermore, because there was no requirement to upload supporting evidence when filling out the checklist, it is feared that the officers will only fill in based on their respective perceptions, potentially resulting in a biased outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 20 Usually, just like in other country, a designated hospital representative was in charge of filling out the checklist. 5 Coordination among hospital units is also difficult due to a lack of technical instruction. Furthermore, because there was no requirement to upload supporting evidence when filling out the checklist, it is feared that the officers will only fill in based on their respective perceptions, potentially resulting in a biased outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This supported the findings of previous research in which the results of completing assessments in Nigeria were not independently verified, potentially leading to response bias. 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many hospitals were not adequately prepared for COVID-19, which is why it was able to spread so quickly and put so much strain on global healthcare systems. A study carried out in Nigeria found that only 15% of the hospitals they surveyed would have been adequately prepared for COVID-19 [ 12 ]. Another study found that hospitals on average in the United States only had around 0.8 beds per 1000 people on a normal day, meaning there were very few beds for COVID-19 patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%